Konsumsi Fast food Sebagai Faktor Risiko Kesehatan Terkait Obesitas dan Sindrom Metabolik pada Remaja : Literature Review - Ahmad Hafidz Fadhilah,; Amirah, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Fast food  consumption among adolescents has increased along with modern lifestyle changes and poses potential long-term health risks. Fast food , which is high in energy, saturated fat, sugar, and sodium, has been associated with obesity and metabolic disorders from an early age. This study aimed to review the relationship between Fast food  consumption as a health risk factor and the occurrence of obesity and metabolic syndrome among adolescents using a literature review approach. Articles were identified through Google Scholar, Garuda, and PubMed databases, including original studies published between 2015 and 2025, available in full text, and examining the association between Fast food  consumption and obesity and/or metabolic syndrome in adolescents. A total of 30 selected articles were analyzed descriptively and synthesized within a health risk management framework. The findings indicated that most studies reported a significant association between Fast food  consumption and obesity among adolescents. Obesity, particularly central obesity, acted as an intermediate condition that increased the risk of developing metabolic syndrome, including dyslipidemia, hypertension, and impaired glucose metabolism. In conclusion, Fast food  consumption is a significant health risk factor for obesity and metabolic syndrome in adolescents, highlighting the need for controlling Fast food  intake through a health risk management approach to prevent non-communicable diseases from an early age.